Cartografias educacionais: regionalização da expansão do ensino secundário em Pernambuco e a interseção entre atores globais e locais (1960–1970) - Santos, Kalline Laira Lima dos [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Esta tese investiga o processo de expansão do ensino secundário em Pernambuco entre as décadas de 1960 e 1970, analisando as relações entre planejamento educacional, regionalização e circulação transnacional de ideias e modelos educacionais. Parte da problematização acerca da articulação entre educação e desenvolvimento regional no contexto de consolidação de políticas de planejamento no Brasil e da crescente atuação de organismos internacionais na formulação de políticas educacionais. Tem como objetivo compreender de que maneira instituições como a Superintendência do Desenvolvimento do Nordeste (SUDENE), a Organização das Nações Unidas para a Educação, a Ciência e a Cultura (UNESCO), o Ministério da Educação e os Centros Regionais de Pesquisas Educacionais participaram da constituição de uma cartografia educacional voltada à expansão do ensino secundário em Pernambuco. A pesquisa fundamenta-se na História da Educação em diálogo com a História Política e mobiliza documentação produzida por organismos internacionais, instituições governamentais e órgãos de planejamento educacional, incluindo relatórios, mapas, estatísticas, legislações, correspondências e documentos técnicos consultados em acervos brasileiros e estrangeiros. Os resultados evidenciam que a expansão do ensino secundário integrou projetos mais amplos de modernização e desenvolvimento regional, nos quais a educação foi concebida como instrumento estratégico de intervenção sobre o território. Demonstram, ainda, que a regionalização da escolarização resultou de processos complexos de negociação, circulação e apropriação de modelos educacionais em diferentes escalas, produzindo configurações desiguais na distribuição das oportunidades escolares. Conclui-se que a expansão do ensino secundário em Pernambuco esteve associada à construção de instrumentos técnicos de planejamento e à circulação internacional de concepções educacionais, revelando a centralidade das relações entre educação, território e desenvolvimento na configuração histórica da escolarização brasileira.

This thesis investigates the expansion of secondary education in the state of Pernambuco, Brazil, between the 1960s and 1970s, examining the relationships between educational planning, regionalization, and the transnational circulation of educational ideas and models. It is grounded in the problematization of the links between education and regional development during a period marked by the consolidation of planning policies in Brazil and the growing influence of international organizations on educational policymaking. The study aims to understand how institutions such as the Superintendence for the Development of the Northeast (SUDENE), the United Nations Educational, Scientific and Cultural Organization (UNESCO), the Ministry of Education, and the Regional Centers for Educational Research contributed to the construction of an educational cartography designed to guide the expansion of secondary education in Pernambuco. Drawing upon the field of History of Education in dialogue with Political History, the research is based on documents produced by international organizations, governmental agencies, and educational planning institutions, including reports, maps, statistics, legislation, correspondence, and technical documents consulted in Brazilian and international archives. The findings demonstrate that the expansion of secondary education was part of broader projects of modernization and regional development in which education was conceived as a strategic instrument for territorial intervention. They further reveal that the regionalization of schooling resulted from complex processes of negotiation, circulation, and appropriation of educational models across different scales, producing unequal configurations in the territorial distribution of educational opportunities. The thesis concludes that the expansion of secondary education in Pernambuco was closely associated with the development of technical planning instruments and the international circulation of educational concepts, highlighting the central role of the relationships between education, territory, and development in the historical configuration of Brazilian schooling.
Educational cartographies: the regionalization of secondary education expansion in Pernambuco and the intersection between global and local actors (1960–1970)
Keywords: Educação - História; Ensino secundário; Planejamento educacional; Planejamento regional; Educação - Cooperação internacional